Controllability of Hilfer fractional Langevin evolution equations - Wang, Haihua; Ku, Junhua (Frontiers in Applied Mathematics and Statistics, 2023)
In this paper, by using the $(α,β)$ resolvent operator and three different fixed point theorems, we discuss the control problem for a class of Hilfer fractional Langevin evolution equations. The existence of mild solutions is proved. Finally, an example is also discussed to illustrated our results.